Toward a sustainable biorefinery using high‐gravity technology. (5th October 2016) - Xiros, Charilaos; Janssen, Matty; Byström, Roberth; Børresen, Børre T.; Cannella, David; Jørgensen, Henning; Koppram, Rakesh; Larsson, Christer; Olsson, Lisbeth; Tillman, Anne‐Marie; Wännström, Sune
Abstract: The realization of process solutions for a sustainable bioeconomy depends on the efficient processing of biomass. High‐gravity technology is one important alternative to realizing such solutions. The aims of this work were to expand the knowledge‐base on lignocellulosic bioconversion processes at high solids content, to advance the current technologies for production of second‐generation liquid biofuels, to evaluate the environmental impact of the proposed process by using life cycle assessment (LCA), and to develop and present a technically, economically, and environmentally sound process at high gravity, i.e., a process operating at the highest possible concentrations of raw material. The results and opinions presented here are the result of a Nordic collaborative study within the framework of the HG Biofuels project. Processes with bioethanol or biobutanol as target products were studied using wheat straw and spruce as interesting Nordic raw materials. During the project, the main scientific, economic, and technical challenges of such a process were identified. Integrated solutions to these challenges were proposed and tested experimentally, using wheat straw and spruce wood at a dry matter content of 30% ( w/w ) as model substrates. The LCA performed revealed the environmental impact of each of the process steps, highlighting the importance of the enzyme dose used for the hydrolysis of the plant biomass, as well as the importance of the fermentation yield. © 2016 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.